2022
DOI: 10.1177/23259671221098749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Injury Rates and Timing in the National Football League

Abstract: Background: The coronavirus 2019 (COVID-19) pandemic resulted in the cancellation of the 2020 National Football League (NFL) preseason and a decreased preseason roster size. The effect of this disruption on athlete injury rates is unknown. Purpose/Hypothesis: The purpose was to quantify the rates of anterior cruciate ligament (ACL), Achilles tendon, and hamstring tendon injuries in NFL players before and after the COVID-19 pandemic. We hypothesized that injury rates in the 2020 season would be higher than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Studies performed by Bailey (2,3,30,35). These studies suggest an increased incidence of injury compared with previous seasons unaffected by 3,30,35). However, Platt et al (32) analyzed the 2020 NFL regular season and found no change in overall incidence of injury or incidence of injury by player position compared with previous seasons.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies performed by Bailey (2,3,30,35). These studies suggest an increased incidence of injury compared with previous seasons unaffected by 3,30,35). However, Platt et al (32) analyzed the 2020 NFL regular season and found no change in overall incidence of injury or incidence of injury by player position compared with previous seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, limited literature has been published looking at the effects of COVID-19 on NFL injury rates (1)(2)(3)(30)(31)(32)35). Studies performed by Bailey (2,3,30,35).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations